Comparison of Principles of Gender Equality in Burgerlijk Wetboek and Marriage Law Regarding the Rights and Obligations of Husband Wife - Yoandini, Elitta; Sarah, Siti; Al Amruzi, M. Fahmi (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
This study examines and compares the principle of gender equality in the regulation of spousal rights and obligations as stipulated in the Burgerlijk Wetboek (Indonesian Civil Code) and Law Number 1 of 1974 on Marriage. The research applies a normative legal method with qualitative analysis. The findings indicate that the Civil Code reflects a patriarchal legal construction that places the husband as the dominant head of the family, while the wife occupies a subordinate position. In contrast, the Marriage Law embodies the spirit of family law reform in Indonesia by recognizing equal rights and status between husband and wife, although it still contains elements of traditional gender role bias. The amendment through Law Number 16 of 2019, which equalizes the minimum age for marriage, serves as an indicator of progress toward achieving gender justice. However, the implementation of these equality norms continues to face challenges from entrenched patriarchal cultural values in society. This study concludes that more substantive legal reform and social transformation are essential to realize a just and equal marital relationship.